Correction: Legal consumer protection – with regards to the rights of hotel services users (2015, Vol. 3, No. 1, p. 98-107) - Maksimović, Nina; Milićević, Rada (Hotel and Tourism Management, 2017)
Correction: Legal consumer protection – with regards to the rights of hotel services users (2015, Vol. 3, No. 1, p. 98-107)